EFEKTIVITAS KONSELING COGNITIVE BEHAVIOR DENGAN TEKNIK REFRAMING UNTUK MENINGKATKAN KEBAHAGIAAN BERBASIS NILAI-NILAI TRI HITA KARANA BAGI REMAJA KORBAN PERCERAIAN - Putri, Ni Wayan Cindy Amelia; Gading, I Ketut; Paramartha, Wayan Eka (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
Happiness is a condition where individuals tend to remember positive experiences rather than negative ones. Happiness can also be defined as a positive emotion that fuels enthusiasm and gives meaning to every individual's actions. According to the local value of Tri Hita Karana, happiness is a harmonious relationship between humans and God (Parahyangan), between humans and others (Pawongan), and between humans and the environment (Palemahan). This study addresses the low happiness of adolescent victims of divorce, which often causes emotional trauma, depression, and difficulties in social adaptation. The impacts of parental divorce include loss of affection, mental stress, and environmental changes, with triggering factors such as economics, conflict, and infidelity. This study tested the effectiveness of Cognitive Behavior counseling using the Reframing technique to increase the happiness of adolescents at the Dana Punia Orphanage, Singaraja. This intervention changed negative thought patterns into positive perspectives through stages such as identifying perceptions, reframing, and follow-up. The hypothesis stated that the intervention was effective in increasing happiness indicators such as spiritual calm and harmonious relationships. This study used a quasi-experimental design with a Pretest-Posttest control group experimental research design with 10 samples of adolescents aged 15-21 years (5 experimental groups, 5 control groups). The intervention consisted of six sessions, measured using a Tri Hita Karana-based happiness questionnaire. Reframing techniques included rational strategies, perception modification, and homework for habituation. Cognitive Behavior Counseling with Reframing integrated with local Tri Hita Karana values effectively restored happiness through cognitive and behavioral changes. This research differs from previous studies by focusing on specific intervention experiments in the Balinese context. ABSTRAKKebahagiaan adalah kondisi individu yang cenderung mengingat pengalaman positif dibandingkan dengan pengalaman negatif. Kebahagiaan juga dapat diartikan sebagai emosi positif yang memicu semangat dan memberikan makna dalam setiap tindakan individu. Menurut nilai lokal Tri Hita Karana, kebahagiaan merupakan keharmonisan hubungan antara manusia dengan Tuhan (Parahyangan), hubungan antara manusia dengan sesama (Pawongan), dan hubungan antara manusia dengan lingkungan (Palemahan). Penelitian ini mengatasi rendahnya kebahagiaan remaja korban perceraian, yang sering menyebabkan trauma emosional, depresi, dan kesulitan adaptasi sosial. Dampak perceraian orang tua termasuk kehilangan kasih sayang, tekanan mental, dan perubahan lingkungan, dengan faktor pemicu seperti ekonomi, konflik, dan perselingkuhan. Menguji efektivitas konseling Cognitive Behavior teknik Reframing untuk meningkatkan kebahagiaan remaja di Panti Asuhan Dana Punia, Singaraja. Intervensi ini mengubah pola pikir negatif menjadi perspektif positif melalui tahapan seperti identifikasi persepsi, reframing, dan tindak lanjut. Hipotesis menyatakan intervensi tersebut efektif dalam meningkatkan indikator kebahagiaan seperti ketenangan spiritual dan hubungan harmonis. Penelitian ini menggunakan desain quasi-eksperimen dengan design penelitian eksperimen Pretest-Posttest control group dengan 10 sampel remaja usia 15-21 tahun (5 kelompok eksperimen, 5 kontrol). Intervensi dilakukan 6 sesi, diukur dengan kuesioner kebahagiaan berbasis Tri Hita Karana. Teknik Reframing meliputi rasional strategi, modifikasi persepsi, dan homework untuk pembiasaan. Konseling Cognitive Behavior dengan Reframing diintegrasikan dengan nilai lokal Tri Hita Karana efektif memulihkan kebahagiaan melalui perubahan kognitif dan perilaku. Penelitian ini membedakan diri dari studi sebelumnya dengan fokus eksperimen intervensi spesifik pada konteks Bali.